PENGARUH KUALITAS PENGAJARAN GURU DAN KEBIASAAN BELAJAR SISWA TERHADAP PRESTASI BELAJAR MATA PELAJARAN EKONOMI PADA SISWA DI SMA NEGERI 6 SURAKARTA TAHUN AJARAN 2017/2018 - -, Nur Aini -; -, Sri Wahyuni -; -, Salman Alfarisy Totalia - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
The research aims to determine: (1) The effect a significantly positive of teaching quality and learning habit to the learning achievement of economic subject of the students at State Senior Secondary School 6 of Surakarta in academic year 2017/2018; (2) The effect a significantly positive of teaching quality to the learning achievement of economic subject of the students at State Senior Secondary School 6 of Surakarta in academic year 2017/2018; (3) The effect a significantly positive of learning habit to the learning achievement of economic subject of the students at State Senior Secondary School 6 of Surakarta in academic year 2017/2018.The method used in this research is descriptive quantitative method. The population of this research was students of class X of social sciences in State Senior Secondary School 6 of Surakarta. 116 students were selected as sample through Proportionate Random Sampling. Data were collected by means of questionnaire, for teaching quality data and learning habit data and documentation for student?s learning achievement data. The data analysis technique used is multiple linier regression analysis technique. The results of the research are as follows: (1) the teaching quality and learning habit has been indicated significantly positive effect the learning achievement of economic subject of the students at State Senior Secondary School 6 of Surakarta in academic year 2017/2018, as indicated by the value of Fstat. = 46,927 >that of Fcrit. = 3,07. (2) the teaching quality has been indicated significantly positive effect the learning achievement of economic subject of the students at State Senior Secondary School 6 of Surakarta in academic year 2017/2018, as indicated by the value of tstat. =9,036> that of tcrit.=1,981. (3) the learning habit has been indicated significantly positive effect the learning achievement of economic subject of the students at State Senior Secondary School 6 of Surakarta in academic year 2017/2018, as indicated by the value of tstat. =7,626> that of tcrit.=1,981.